Sunday

March 29, 2015

March 29, 2015

Posted by **Jess** on Wednesday, February 7, 2007 at 5:49pm.

cos(2x-180) - sin(x-90)=0

my work:

cos2xcos180 + sin2xsin180= sinxcos90 - sin90cosx

-cos2x - sin2x= cosx

-cos^2x + sin^2x -2sinxcosx=cosx

I'm stuck here. I tried subtracting cosx from both sides and making sin^2x into 1- cos^2x, but I still can't seem to solve the problem.

**Answer this Question**

**Related Questions**

Trigonometry - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/...

Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...

Trig....... - I need to prove that the following is true. Thanks (2tanx /1-tan^x...

RESPONSE to PreCalc Question - h t t p : / / w w w . j i s k h a . c o m / d i s...

Trig (Last URGENT) - sin2x+cosx=0 , [-180,180) = 2sinxcosx+cosx=0 = cosx(2sinx+1...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Precalculus/Trig - I can't seem to prove these trig identities and would really ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Calc II - For the following question, we need to find the length of the polar ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...